1998
DOI: 10.1002/(sici)1521-4079(1998)33:2<241::aid-crat241>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Bridgman Growth and Characterization of LuAlO3—Ce3+ Scintillator Crystals

Abstract: Chemical and structural effects in LuAlO3‐Ce3+ single crystals grown by the Bridgman method were studied using spectral emission, x‐ray, etching and optical techniques. The Ce concentration distribution was found to exhibit the normal freeze behavior with partition coefficient of 0,17. The expansion of the unit cell volume due to incorporation of Ce was measured. Dislocation etch pits were revealed on (010), (100) and (001) crystal faces. Thermal expansion behavior of LuAlO3 was studied along the major crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Considering the lattice constants of LuAP, Petrosyan et al reported that the lattice constants a, b and c are determined to be 5.100 Å, 5.330 Å and 7.294 Å, respectively. 28) In comparison with the lattice constants of LuYAP obtained in this study with the results of LuAP, the lattice constants of a and c were negatively correlated with Lu concentration, while b was almost constant regardless Lu concentration. This is because the ionic radii of Y 3+ (8-coordination) and Lu 3+ (8-coordination) are 1.019 Å and 0.977 Å, respectively, which suggests that the increase of Lu concentration caused the decrease of the lattice constants.…”
Section: Resultssupporting
confidence: 57%
“…Considering the lattice constants of LuAP, Petrosyan et al reported that the lattice constants a, b and c are determined to be 5.100 Å, 5.330 Å and 7.294 Å, respectively. 28) In comparison with the lattice constants of LuYAP obtained in this study with the results of LuAP, the lattice constants of a and c were negatively correlated with Lu concentration, while b was almost constant regardless Lu concentration. This is because the ionic radii of Y 3+ (8-coordination) and Lu 3+ (8-coordination) are 1.019 Å and 0.977 Å, respectively, which suggests that the increase of Lu concentration caused the decrease of the lattice constants.…”
Section: Resultssupporting
confidence: 57%
“…The problem of twins was reported recently for YAP:Nd single crystal growth [229]. The boules of LuAP : Ce grown by the Bridgman method [219] approach dimensions of diameter about 1.2 cm  6 cm length with similar Ce concentrations. Mixed (Y±Lu)AP : Ce crystals grown by the Czochralski method at CRYTUR Ltd. have typical dimensions of diameter about 2 cm  6 cm length.…”
Section: Ce 3+ -Doped Aluminium Perovskites Xalo 3 : Ce (X Y Lu Y±lu)mentioning
confidence: 80%
“…Spectrally unresolved scintillation decay of a YAlO 3 : Ce 3+ single crystal excited by 22 Na radioisotope. Slower decay components and background enhancement are related to the delayed radiative recombination of charge carriers at Ce 3+ emission centres LuAP single crystal (density 8.35 g/cm 3 ) was intensively studied and was grown mainly by the Czochralski method, but also by the Bridgman method [219]. Optical properties of LuAP : Ce are in all aspects similar to those of YAP : Ce including the unwanted absorption tail around 330 nm which causes a significant decrease of LY for larger (about 10 to 15 mm in length) samples [220].…”
Section: Ce 3+ -Doped Aluminium Perovskites Xalo 3 : Ce (X Y Lu Y±lu)mentioning
confidence: 99%
“…Its heavier structural analog, LuAlO 3 (LuAP) with a high density of 8.35 g cm −3 and an effective atomic number as high as 64.9, has attracted attention from the scintillation material community since 1990s. 22–25 However, due to the very low stability of the perovskite phase and difficulties in crystal growth, its commercialization was not successful even in the case of a more stable Y-admixed LuAP (LuYAP) variant. 26 Similar to the garnet counterparts, 7–9 the anti-site defects (rare-earth ions substituting Al 3+ in the AlO 6 octahedra) and related deterioration of scintillation characteristics can also be observed in perovskites.…”
Section: Introductionmentioning
confidence: 99%